Food Preferences and Diet Patterns of Tribal Population of India: A Review Study from a Nutrition Lens - Barik, Sushanta Kumar; Turuk, Jyotirmayee; Khemnar, Annasaheb S; Harke, Sanjay N; Mulay, Manjushree V.; Kulkarni, Smita Sitaram; Deshmukh, Ashish S.; Dhoble, Sanjay J; Mohanty, Keshar Kunja (Current Perspectives in Agriculture and Food Science Vol. 9, 2024)
The diet, nutrition, nutritional value and socio-economic status of tribal populations in various states of India are reported. India is a diversified country with half of the vulnerable tribal population groups of the world. The dietary habits and nutritional patterns of the tribal population are different from the rest of the population of India. The tribal populations of India are socio-economically disadvantaged compared to the other population groups of India. The tribal populations of India have various nutritional health problems due to cultural characteristics, socio-economic development, and geographical isolation in a specified region of India. The natural forest ecosystem is the living place of the tribal population of India from where they take diet and nutrition supplements to sustain their life. Nutrition, health, and child malnutrition are the key determinants in the life of the tribal population of India. As fifty percent tribal population of the world is living in India, it is merely emphasizing the consumption of diets and nutrition among adults, adolescents, and children and the malnutrition of the various tribal groups of India. The assessment and monitoring of diet, nutrition, and nutritional value of various tribes of different states of India is very essential. Thus, we focused on the collection of information on the types of diets and their dietary habits, nutrition, and nutritional status of the tribal population in various states of India.